Budidaya Udang Vaname (Litopenaeus vanammei) yang Dibudidayakan secara Semi Intensif di TEFA Poltek KP Kupang - Sianturi, Ion Tarsardo; Maniko, Abia Pelipus (Politeknik Kelautan dan Perikanan Bone, 2023)
Vaname shrimp (Litopenaeus vannamei) has high economic value so it is widely cultivated in Indonesia. Vaname shrimp (L. vannamei) cultivation has been widely developed in Indonesia because of several perceived advantages, including high productivity, responsiveness to feed, more resistance to disease, abundant availability of fry and a fairly large market area. The aim of this research was to determine the growth performance of semi-intensive vaname shrimp (L. vannamei) cultivation in Kupang City, East Nusa Tenggara. The data collection methods used included observation and active participation. Stages in cultivating vaname shrimp (L. vannamei) include pond preparation, fry stocking, feed and air quality management, pest and disease control, harvesting and marketing. The activities were carried out from February 5, 2023 to Juny 6, 2023. The research results obtained were production value of 927 kg, SR value of 90%, FCR value of 1.94, highest ADG and ABW values of 0.43 g/ day and 21 g, respectively, at DOC 90, and the R/C ratio value of 2.4, which indicated this business experienced profits and worth developing.